2012
DOI: 10.2139/ssrn.1983342
|View full text |Cite
|
Sign up to set email alerts
|

Remanufacturing, Third-Party Competition, and Consumers' Perceived Value of New Products

Abstract: I n this paper, we investigate whether and how the presence of remanufactured products and the identity of the remanufacturer influence the perceived value of new products through a series of behavioral experiments. Our results demonstrate that the presence of products remanufactured and sold by the original equipment manufacturer (OEM) can reduce the perceived value of new products by up to 8%. However, the presence of thirdparty-remanufactured products can increase the perceived value of new products by up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 47 publications
2
41
0
3
Order By: Relevance
“…Using these results, he shows that (contrary to conventional wisdom) a firm should generally set a much lower price for their remanufactured products than the myopic price that ignores the presence of new products. Also leveraging behavioral results, Agrawal et al (2012) show that an Original Equipment Manufacturer (OEM) reduces the perceived quality of their new products when they remanufacture their own goods. However, they show that the perceived quality of an OEM's new products increases with the presence of a third-party remanufacturer.…”
Section: Forward Supply Chainmentioning
confidence: 99%
“…Using these results, he shows that (contrary to conventional wisdom) a firm should generally set a much lower price for their remanufactured products than the myopic price that ignores the presence of new products. Also leveraging behavioral results, Agrawal et al (2012) show that an Original Equipment Manufacturer (OEM) reduces the perceived quality of their new products when they remanufacture their own goods. However, they show that the perceived quality of an OEM's new products increases with the presence of a third-party remanufacturer.…”
Section: Forward Supply Chainmentioning
confidence: 99%
“…Ferguson and Toktay [16] analyzed the competition between new and remanufactured products in monopoly and duopoly environments and found that a firm may choose to remanufacture or preemptively collect its used products to deter the entry of remanufacturers. However, Agrawal et al [17] demonstrated that the presence of third-party-remanufactured products can increase the perceived value of new products. Wu and Zhou [18] also found that competing OEMs without remanufacturing capacities sometimes benefit from the entry of IRs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also leveraging behavioral results, Agrawal et al (2012) show that an original equipment manufacturer (OEM) reduces the perceived quality of their new products when they remanufacture their own goods. However, they show that the perceived quality of an OEM's new products increases with the presence of a third-party remanufacturer.…”
Section: Closed-loop Supply Chainmentioning
confidence: 99%